Priorities to reduce the burden of stroke in Latin American countries. Issue 7 (July 2019) - Ouriques Martins, Sheila C; Sacks, Claudio; Hacke, Werner; Brainin, Michael; de Assis Figueiredo, Francisco; Marques Pontes-Neto, Octávio; Lavados Germain, Pablo M; Marinho, Maria F; Hoppe Wiegering, Arnold; Vaca McGhie, Diana; Cruz-Flores, Salvador; Ameriso, Sebastian F; et al.
Summary: The large and increasing burden of stroke in Latin American countries, and the need to meet the UN and WHO requirements for reducing the burden from non-communicable disorders (including stroke), brought together stroke experts and representatives of the Ministries of Health of 13 Latin American countries for the 1st Latin American Stroke Ministerial meeting in Gramado, Brazil, to discuss the problem and identify ways of cooperating to reduce the burden of stroke in the region. Discussions were focused on the regional and country-specific activities associated with stroke prevention and treatment, including public stroke awareness, prevention strategies, delivery and organisation of care, clinical practice gaps, and unmet needs. The meeting culminated with the adoption of the special Gramado Declaration, signed by all Ministerial officials who attended the meeting. With agreed priorities for stroke prevention, treatment, and research, an opportunity now exists to translate this Declaration into an action plan to reduce the burden of stroke.